Calreticulin expression in human cardiac myocytes induces ER stress‐associated apoptosis - Michael W. Stoner; Charles F. McTiernan; Iain Scott; Janet R. Manning (Physiological Reports, 2020)
Abstract The global burden of heart failure following myocardial ischemia‐reperfusion (IR) injury is a growing problem. One pathway that is key to understanding the progression of myocardial infarction and IR injury is the endoplasmic reticulum (ER) stress pathway, which contributes to apoptosis signaling and tissue death. The role of calreticulin in the progression of ER stress remains controversial. We hypothesized that calreticulin induction drives proapoptotic signaling in response to ER stress. We find here that calreticulin is upregulated in human ischemic heart failure cardiac tissue, as well as simulated hypoxia and reoxygenation (H/R) and thapsigargin‐mediated ER stress. To test the impact of direct modulation of calreticulin expression on ER stress‐induced apoptosis, human cardiac‐derived AC16 cells with stable overexpression or silencing of calreticulin were subjected to thapsigargin treatment, and markers of apoptosis were evaluated. It was found that overexpression of calreticulin promotes apoptosis, while a partial knockdown protects against the expression of caspase 12, CHOP, and reduces thapsigargin‐driven TUNEL staining. These data shed light on the role that calreticulin plays in apoptosis signaling during ER stress in cardiac cells.